Screening for Depression and Anxiety in Patients with Active Uveitis - AKMAN, MEHMET (TAYLOR & FRANCIS INC, 2018)
Purpose: To screen for psychological disorders in patients with active uveitis. Methods: Patients were screened for depression (BDI-II), state anxiety (STAI-I), VR-QOL (NEI-VFQ-25), and HR-QOL (SF-36). Association of depression and anxiety with sociodemographic and clinical parameters and with VR-QOL and HR-QOL were analyzed. Multivariate linear regression models were constructed for NEI-VFQ-25 and SF-36 subscales. Results: Of 99 patients, 37.3% screened positive for depression and 52.5% for anxiety. Depressed patients had lower visual acuity in the better seeing eye (p = 0.013) and more frequently panuveitis (p = 0.018). Anxious patients were younger (p = 0.009), had earlier onset of uveitis (p = 0.015), and had more frequently panuveitis (p = 0.016). Bivariate comparisons showed significant associations between psychological disorders and VR-QOL and HR-QOL. Significant bivariate associations were mostly lost in multivariate analyses for anxiety, but were preserved for depression. Conclusions: A positive screening test for depression and anxiety is common in patients with uveitis. Low vision and panuveitis are associated with depression. Depression is associated with impairment of VR-QOL and HR-QOL.
Keywords: Anxiety; BDI-II; depression; general health; NEI-VFQ-25; quality of life; SF-36; STAI-I; uveitis; vision; QUALITY-OF-LIFE; ANTERIOR UVEITIS; VISUAL-ACUITY; STANDARDIZATION; COMORBIDITY; PREVALENCE; DISORDERS; IMPACT; MOOD